Assessing Shared Value in Business Management: Developing A Measurement Scale - Anna SIBINSKA; Wioletta KRAWIEC (Communications of International Proceedings, 2023)
In the literature, the Creating Shared Value concept has shown a wide range of interest in both the academic and business communities. One area of interest to researchers is the search for metrics to measure CSV. However, an appropriate scale for measuring shared value is still lacking. Our study addresses this research gap by proposing the creation of dimensions of the CSV construct, as well as the items comprising each of these dimensions. The paper presents the results obtained from a Delphi Study (two rounds) with experts representing academics and business partisans. The study identified four dimensions such as social value creation (SVC), environmental value creation (EnVC), economic value creation (EVC) and innovation value creation (IVC). In addition, experts' statements on the items were verified through qualitative assessment. The researchers see a need to develop future research using both qualitative and quantitative methods to develop an entire CSV scale to validate the measurement tool. The article includes implications for managers and executives of business organizations to evaluate the effects of their value creation activities.
Keywords: shared value; social value creation; economic value creation; environmental value creation; innovation value creation.